Pendidikan Kesehatan Tentang Anemia dan Stunting Pada Ibu Hamil - Asti Andriyani; Kuswati Kuswati (Yayasan Inspirasi El Burhani, 2023)
Introduction: Anemia during pregnancy is a public health problem, especially in developing countries, and is associated with poor pregnancy outcomes. During pregnancy, iron deficiency anemia adversely affects maternal and fetal well-being and is associated with increased fetal morbidity and mortality. Affected mothers often experience difficulty breathing, fainting, fatigue, heart palpitations, and difficulty sleeping. They also have an increased risk of developing perinatal infections, pre-eclampsia, and bleeding. Babies whose birth weight is less than 2,500 grams will carry the risk of death and impaired child growth, including the risk of being stunted if not handled properly. Objective: This activity aims to increase pregnant women's knowledge about anemia and stunting so that pregnant women can have a healthy pregnancy. Methods: Health education activities about anemia and stunting were given to pregnant women in Joton Keboarum village, Klaten. This activity began with a coordination meeting with the village midwife regarding the implementation of providing anemia and stunting health education. The media used is material in the form of Power Point, which is provided with the help of an OHP. Results: The most knowledge of pregnant women before being given counseling was poor knowledge, as many as 9 pregnant women (69.2%), while the knowledge of pregnant women after being given counseling was mostly good knowledge, as many as 11 pregnant women (84.6%). Conclusion : there was an increase in knowledge about anemia and stunting after being given health education